Asset Redeployability and Corporate Tax Avoidance. (25th January 2021) - Hasan, Mostafa Monzur; Habib, Ahsan; Alam, Nurul
Abstract : Using a large sample of US data, we examine the relationship between asset redeployability and corporate tax avoidance. We also examine the extent to which asset redeployability influences tax avoidance directly and indirectly (through financing constraints channel). We find a significant negative relationship between asset redeployability and tax avoidance, implying that firms with more redeployable assets tend to engage in less tax avoidance. We also confirm that asset redeployability reduces tax avoidance both directly and indirectly (through reducing financing constraints). These results are robust to alternative specifications of asset redeployability and corporate tax avoidance, and to the use of a two‐stage least squares (2SLS) analysis to mitigate any endogeneity concerns relating to omitted variables, reverse causality, and model misspecification. Overall, these findings extend our existing understanding of the implication of asset redeployability in an accounting context and demonstrate that redeployability of assets has important implication for corporate tax planning.